Infantile Sweet syndrome following MMRV vaccine. Issue 1 (13th November 2022) - Itzhaki Gabay, Sapir; Samueli, Benzion; Test, Gidon; Valdman‐Grinshpoun, Yuliya; Horev, Amir
Abstract: Sweet syndrome (SS), also called acute febrile neutrophilic dermatosis, is rare in the pediatric population, especially in infants and neonates. We present a case of infantile SS that developed 1 day after the MMRV vaccine; we suggest a possible causal relationship between the MMRV vaccine and SS.